A vibrational spectroscopic study of clathrates of resorcarene-based cavitands - Schatz, Jürgen; et al. (Journal of Physical Organic Chemistry, 2001)
By comparison of the fully assigned vibrational spectra obtained for resorcarene-based cavitands 2a and 2b, their clathrates with toluene and ethanol respectively, and free guest molecules, good structural models for the clathrates could be obtained merely based on fourier transform infrared data. Using this novel technique, various different interactions between the host and guest in the solid state as well as the orientation of the included guest could be identified. In the case of cavitand 2a, the model obtained by this methodology could be validated by comparison with an experimental crystal structure analysis. Copyright © 2001 John Wiley & Sons, Ltd.